2016
DOI: 10.1021/acs.chemmater.6b00474
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Shape-Memory Aerogels from Thiol–Ene Networks

Abstract: Thermoresponsive shape-memory polymer aerogels have been produced from thiol–ene networks of 1,6-hexanedithiol, pentaerythritol tetrakis­(3-mercaptopropionate), and triallyl-1,3,5-triazine-2,4,6-trione. The thiol–ene networks form organogels with either acetonitrile or acetone as the solvent, which can be subsequently removed using supercritical CO2 extraction. The resulting aerogels have nearly quantitative shape fixing and shape recovery with a glass transition temperature ranging from 42 to 64 °C, which ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 44 publications
0
30
0
4
Order By: Relevance
“…Shape‐memory materials, which have been widely used in the field of drug delivery system and aerospace, are one kind of smart materials that have the functionality to keep a temporary shape, and can recover to their original shape under an external stimulation, such as water stimulation, heat stimulation, light stimulation, electrical stimulation, and so on …”
Section: Resultsmentioning
confidence: 99%
“…Shape‐memory materials, which have been widely used in the field of drug delivery system and aerospace, are one kind of smart materials that have the functionality to keep a temporary shape, and can recover to their original shape under an external stimulation, such as water stimulation, heat stimulation, light stimulation, electrical stimulation, and so on …”
Section: Resultsmentioning
confidence: 99%
“…Die Vereinigung der Zellen und die mangelnde Integrität der Zellwände führen bei der Blowing‐Methode oft zu einer makroporösen, offenen Zellstruktur. Ein sehr gutes Beispiel für einen Schwamm mit größtenteils offener Zellstruktur ergab eine PP/PTFE‐Mischung, die durch einen Extrusionsprozess mit CO 2 gewonnen wurde . Interessanterweise konnte die Aufnahmerate von Benzinen oder organischen Flüssigkeiten dieser Schwämme mit zusätzlicher Ultraschallbehandlung signifikant verändert werden.…”
Section: Methoden Zur Herstellung Makroporöser Schwämmeunclassified
“…In Abhängigkeit von der Trocknungsmethode (Verdunstung, atmosphärische oder überkritische Trocknung) wird der Sol‐Gel‐Prozess (Abbildung a) größtenteils zur Herstellung von Schwämmen als Monolithe, Aerogele, Ambigele oder Xerogele eingesetzt. Abbildung b zeigt vier typische Beispiele für 3D‐Thiol‐En‐Netzwerke, ligninbasierte Xerogele, CNT‐Schwämme und Graphen/Kohlenstoff‐Aerogele . Xerogele und Ambigele können ihre Form während des Trocknens wegen der schwachen Netzstruktur verlieren und stark schrumpfen, wohingegen Aerogele eine höhere Formstabilität aufweisen.…”
Section: Methoden Zur Herstellung Makroporöser Schwämmeunclassified
See 1 more Smart Citation
“…However, to the best of our knowledge, there have been very few reports about shape memory aerogels . Rowan and coworkers developed a thermal responsive shape memory aerogel from a thiol‐ene network with a glass temperature above room temperature, and showed that it displays very good shape memory performance. However, this shape memory aerogel is produced from an organogel.…”
Section: Compressive Properties and Shape Memory Performance Of The Cmentioning
confidence: 99%